1993
DOI: 10.1093/oxfordjournals.jbchem.a124251
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Preliminary X-Ray Studies on Pseudoazurin from Achromobacter cycloclastes IAM10131

Abstract: New crystals of a blue copper protein, pseudoazurin from denitrifier Achromobacter cycloclastes IAM1013, have been obtained by means of vapor diffusion with ammonium sulfate as a precipitant at pH 6.0 and 4 degrees C. The crystals belong to the orthorhombic system, space group P2(1)2(1)2(1), with unit cell dimensions of a = 56.69(2), b = 61.53(2), and c = 30.20(1) A. The asymmetric unit includes one molecule of pseudoazurin with a Vm value of 2.04 A3/Da. The crystals are so stable against X-ray irradiation tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…More recently, the x-ray structure of pseudoazurin from A. cycloclastes has been reported ( Fig. 1) (16), and the structure is almost identical to that of pseudoazurin from A. faecalis (11,12) and Pseudomonas AM1 (17).…”
Section: ؊1mentioning
confidence: 66%
“…More recently, the x-ray structure of pseudoazurin from A. cycloclastes has been reported ( Fig. 1) (16), and the structure is almost identical to that of pseudoazurin from A. faecalis (11,12) and Pseudomonas AM1 (17).…”
Section: ؊1mentioning
confidence: 66%
“…Data Collection and Processing-The crystallization (0.1 M potassium phosphate buffer (pH 6.0)) and structural analysis of oxidized pseudoazurin from A. cycloclastes were performed as described previously (26). The data with high resolution was collected with synchrotron radiation at the BL6A 2 station of 2.5 GeV energy produced by the storage ring in the Photon Factory, the National Laboratory for High Energy Physics (KEK), Tsukuba, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary crystallographic studies of A. cycloclastes pseudoazurin were reported by Turley et al (25), but the crystals obtained were too thin for x-ray diffraction data to be obtained. We have previously reported the crystallization and preliminary x-ray studies on oxidized pseudoazurin from A. cycloclastes at pH 6.0 (26). In this work single crystals of oxidized and reduced pseudoazurin with high resolutional diffraction spots were obtained at pH 6.0.…”
mentioning
confidence: 90%
“…The blue copper site in PAz has a distorted tetrahedral geometry showing a highly anisotropic electron paramagnetic resonance spectrum, which is a mixture of axial and rhombic signals (Abdelhamid et al, 2007;Yamaguchi et al, 2016). As of January 2017, structures of PAzes from Alcaligenes faecalis (Petratos et al, 1987(Petratos et al, , 1988, Achromobacter cycloclastes (Inoue et al, 1993), Methylobacterium extorquens (Inoue et al, 1994), Paracoccus pantrophus (Williams et al, 1995), Hyphomicrobium denitrificans (Hira et al, 2009a) and Shinorhizobium meliloti (Laming et al, 2012) have been reported. PAz from A. faecalis (Af PAz) was the first PAz for which the structure was determined via X-ray crystallography (Petratos et al, 1987), and more than a third of the PAz structures deposited in the Protein Data Bank (PDB) are of PAz from A. faecalis.…”
Section: Introductionmentioning
confidence: 99%